دور التغطية في علاج الغمش (الكسل الوظيفي) عند الأطفال بين (5–9) سنوات (خبرة مشفى الأسد الجامعي) - تعتاع, عبد القادر; رجب, محمود; سرحيل, مجدولين (Latakia University Journal -Medical Sciences Series, 2019)
تضمنت الدراسة تطبيق التغطية كعلاج للغمش ( الكسل الوظيفي ) عند / 20 / طفلاً أعمارهم بين ( 5 – 9) سنوات من مراجعي العيادة العينية في مشفى الأسد الجامعي بين عامي ( 2006 - 2007 ) والذين عانوا من غمش ناجم عن أسباب انكسارية, حيث تمت تغطية العين السليمة من دون انقطاع لعدد من الأسابيع يساوي العمر بالسنوات وكانت النتائج كما يأتي: - تحسنت القدرة البصرية لدى جميع الأطفال الذين طبقت لديهم هذه الطريقة لعلاج الغمش على الأقل بمقدار سطرين على لوحة سنلن. - لم تصب العين السليمة بالغمش لدى أي طفل من مجموعة الدراسة بنتيجة التغطية المستمرة, وذلك بفضل المراقبة اللصيقة الأسبوعية. - كلما كان عمر الطفل أصغر كانت فرصة تحسن القدرة البصرية لديه أكبر وينصح بالتغطية المبكرة والمراقبة المستمرة. The study included 20 children between ( 5 – 9 ) years old, whose amblyopia was due to anisometropia between the years ( 2006 – 2007 ) at the Hospital Ophthalmic Clinic. In these children, covering eye was used as a method of treating amblyopia (Lazy eye). In this study, the healthy eye was covered for a number of weeks equal to the age in years without interruption. The results were as follows: The visual acuity improved in all children who were treated for amblyopia by this way at least two lines at the snelen's card. The healthy eye had not amblyopia due to continuous covering in all children and due to close weakly observation. The younger the child is the better the result is. So, we recommend early covering and continuous observation.